ANALISIS PERENCANAAN STRATEGIS SUMBER DAYA MANUSIA PENDIDIKAN DAN SARANA DAN PRASARANA DI STKIP NASIONAL PADANG PARIAMAN - Wage Ummami (Jurnal Dedikasi Pendidikan, 2022)
Educational Planning aims to achieve the learning process effectively and efficiently. For this reason, human educational resources are needed who have the competence and the availability of adequate facilities and infrastructure. The method used in this study is qualitative. Data were collected by interview and documentation study. The data were analyzed qualitatively, and the triangulation technique was used to ensure the validity of the data. The research findings show that the strategic planning made by the National STKIP, both planning for educational human resources and planning for facilities and infrastructure, is good. However, there are still shortcomings, such as the lack of sourcebooks in the library that will support the learning process. Therefore, it needs attention from educational organizations to achieve the vision and mission of educational organizations.